Functions of and communication behavior on twitter after the 2015 Nepal earthquake - Malasig, Bryan James C.; Quinto, Edward Jay M. (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper looked into how Twitter was used by users three days after the 2015 Nepal earthquake and which communication behavior were reflected in the microblogs. Grounded on the Uses and Gratifications Theory (U&GT) and the Situational Theory of Publics (STP), this risk and crisis communication study proceeded with a content analysis of 300 tweets per day mined from April 26 to 28, 2015. After data mining, inter-rating schemes which involved four trained raters sat down to analyze the data based on the research problems. Results showed that the top function of Twitter was the helping function followed by information, communication, and political functions, respectively. Although the predominance of these functions were uniquely different compared with findings in previous studies, results revealed that certain functions of Twitter persisted across various crises. In addition, most users exhibited problem-facing behavior while only a number of users showed constrained behavior. This implied that those who took to Twitter possessed high problem recognition of the crisis and point to how Twitter was used to spread information, making it a very useful social media tool during a crisis. Moreover, results supported Grunig (2013) who argued that, in times of crisis, people become active users of social media tools. Implications for risk and crisis communication plans based on the findings of the study are discussed.